THE ANLGOPHONE TITLES OF THE STARS OF WORLD LITERATURE EDITION (Journal of Contemporary Philology, 2020)
Between 2008 and 2016, the ministries of culture and education of the Republic of Macedonia launched a massive project involving the translation and publishing of literature. The bulkiest of these projects was the 560 volume titled Stars of World Literature. The aim of my research was to create a database documenting the Anglophone titles included in the edition and to further analyze the basic characteristics of the titles included in the edition, such as the very title itself (the translated individual work or collection of works), the title’s author, the publishing house, the translator of the title and the author of the afterword. The analysis takes into account variables such as the century of publication, the genre and subgenre, the gender of the author, translator and author of afterword, and examines the cross tabulation between translator and publishing house, translator and genre, as well as author of afterword and genre.
Keywords: literary translation; world literature; Аnglophone literature; translation from English into Macedonian; Stars of World Literature